The Dialogue of Hikma: Generating Harmony in MuslimNon-Muslim Relations - Suraya Sintang; Khadijah Mohd Khambali @ Hambali; Azizan Baharuddin; Nurhanisah Senin (2016)
This article seeks to explain the concept of the dialogue of hikma as a qur'anic principle in developing harmony in Muslimnon-Muslim relations. Living together harmoniously is essential in a community made up of a myriad of cultures and religions. Efforts to create harmony can be realized through the dialogue of hikma and by inculcating it as the culture in daily life interaction. This is truly essential in the context of mixed-faith families. In order to explore how the dialogue of hikma can be applied in Muslimnon-Muslim relations, this article examines the experience of Muslim converts living together with their non-Muslim families of origin. The research was conducted through in-depth interviews with selected Muslim converts from a variety of cultural backgrounds, living in the area of Kota Kinabalu, Sabah. The results indicate that Muslim converts share similar experiences in applying the dialogue of hikma as a mechanism for solving family problem arising as a result of conversion to Islam.